PRATICES IN THE PRÁXIS: ADVANCES AND LIMITS PROMOVED BY ESCOLA DA TERRA PROGRAM IN THE COUNTRYSIDE SCHOOLS OF IGARASSU/PE - Moisés de Melo Santana; Rigoberto de Melo Arantes (Universidade Federal do Norte do Tocantins, 2020)
Bearing in mind that Countryside Education, with a divergent constitutive logic of the capitalist one and that it involves knowledge, cultures and space-times of its own, aims at the development of the field from its subjects and not at the non-deterritorialization, subalternization or expropriation of their way of living, we analyze, according to the perspectives of Freire (1987), Souza (2007) e Saviani (2013) , the changes provoked in the pedagogical practices of the rural educators who participated in the second edition of the Escola da Terra Program, in the municipality of Igarassu-PE. We proposed, with the Content Analysis, a qualitative-interpretative approach both of signification units, semi-structured interviews, which included managers of the Education Department of the municipality of Igarassu and five educators of the countryside schools named for the Improvement Course in Countryside Education for Teachers of Schools of the Countryside and Quilombolas. We believe that the results of these analyzes not only pointed to the feasibility of future continuing education for educators in the municipality of Igarassu, based on the necessary dialogue between these critical pedagogical theories and the Countryside Education, but also to how they can contribute to the struggle for a culture that guarantees alternatives to the current development model and that cooperates with the construction of another education project for another society.